Does the Addition of Active Body Warming to In-line Intravenous Fluid Warming Prevent Maternal Hypothermia During Elective Caesarean Section? A Randomized Controlled Trial. Issue 2 (June 2018) - Chebbout, R.; Newton, R.S.; Walters, M.; Wrench, I.J.; Woolnough, M.
Abstract : ( Int J Obstet Anesth . 2017;31:37–44) Inadvertent perioperative hypothermia (IPH), defined as a core temperature <36°C, is a common occurrence during elective cesarean section with rates as high as 50% reported. Despite IPH occurring so frequently, active body warming is not commonly used during cesarean section nor are there guidelines for its use in obstetric populations. In the United Kingdom only 16% of obstetric units routinely use active body warming. The goal of the current study was to determine if the use of active body warming, either forced air warming or conduction mattress warming, provided additional benefit during cesarean section when warming of intravenous fluids was also utilized.